Comunicação pública para cidadania no avanço das redes sociais oficiais - Rothberg, Danilo [UNESP]; Valença, Amanda da Silva (My University, 2014)
The advancement in the deployment of social networks by governments can generate public communication initiatives, which may contribute to the strengthening of citizenship, understood as the exercise of the right to information about public management. This article describes results of research which assessed, through content analysis, the breadth and depth of information offered by the state government of São Paulo in news stories accessed through the social networks Twitter, YouTube, Facebook and Orkut which publicize purposes, lines of action and limits of public policies of immediate impact for citizenship, in the areas of welfare, health, education and environment. Results indicate that the analyzed sample contains, on average, from 28% to 40% of all information deemed necessary for the comprehensive and plural characterization of a public policy, according to the theoretical-methodological context of the research.

O avanço da exploração das redes sociais por governos pode gerar iniciativas de comunicação pública capazes de contribuir para o aprofundamento da cidadania, pensada como exercício do direito à informação sobre gestão pública. Este artigo descreve resultados de pesquisa que avaliou, através de análise de conteúdo, a abrangência e a profundidade da informação oferecida pelo governo do Estado de São Paulo em textos noticiosos acessados através das redes sociais Twitter, YouTube, Facebook e Orkut para divulgar propósitos, linhas de ação e limites de políticas públicas de impacto imediato para a cidadania, das áreas de assistência social, saúde, educação e meio ambiente. Os resultados indicam que a amostra analisada contém, em média, entre 28% e 40% do total de informações consideradas como necessárias para a caracterização abrangente e plural das políticas públicas enfocadas, segundo o contexto teórico-metodológico da pesquisa.
Keywords: Digital democracy; Social media; Public policy; Information; Democracia digital; Mídias sociais; Políticas públicas; Informação